The Influence of Marketing Mix (7ps) on Consumer Satisfaction Digital MSMEs - Kurniawan, Hendra; Astuti, Miguna; Sembiring, Rosali; Nastiti, Heni (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of the marketing mix (7Ps), consisting of product, price, place, promotion, people, physical evidence, and process, on consumer satisfaction in digital SMEs. A quantitative approach was employed by distributing questionnaires to digital SME consumers, and the data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The findings reveal that three variables, namely product, place, and physical evidence, significantly affect consumer satisfaction. Products are perceived to meet consumer needs with sufficient variety and clear information, place emerges as the most dominant factor by providing easy access to shipping and payment information, ratings, and reviews, while physical evidence supports satisfaction through clear platform design and informative product visuals. In contrast, price, promotion, people, and process do not significantly influence satisfaction. These results indicate that digital SME consumers prioritize information accessibility, visual quality, and platform reliability over low prices or excessive promotion. The study offers practical implications for digital SMEs to strengthen visual presentation and information clarity while suggesting future research to incorporate variables such as digital trust and user experience to achieve more comprehensive findings.